Identification of Rice Field Potential Using a Geographic Information System Approach in Sambas Regency - Romiyanto, Romiyanto; Agustine, Leony (Jurnal Biologi Tropis, 2026)
Sustainable food cropland protection is similar to the system and process of planning and determining, developing, utilizing, guiding, controlling, and supervising sustainable food cropland and its areas. This study aims to determine the distribution and changes in the intended rice fields, especially in Sambas Regency, West Kalimantan Province. The research methodology refers to the Decree of the Director General of Agricultural Infrastructure and Facilities Number 14/KPTS/SR/B/01/2022 concerning Technical Guidelines for Recommendations for Sustainable Food Cropland Protection. The initial stage of implementation is collecting data from relevant agencies, then creating a work map, collecting field data (groundcheck) in the form of open camera photos at 4,213 points. Then, field data processing is carried out and then the preparation of updated raw rice field data. The results of the RPLP2B study in Sambas Regency show that based on the type of irrigation, rice fields in Sambas Regency are identified as technical irrigated rice fields with an area of ± 643.12 ha, non-technical irrigation ± 16,415.69 ha, and non-irrigated rice fields ± 26,976.67 ha, the area of rice fields with IP 100 reaches ± 10,091.15 ha, IP 150 covers an area of ± 5,614.59 ha, IP 200 covers an area of ± 27,943.68 ha, IP 250 covers an area of  ± 50.43 ha, and the area of land with IP 300 covers an area of ± 335.64 ha. The conclusion is that the potential of rice fields in Sambas Regency is as follows: Of the total 43,508.29 ha of raw rice fields, only 93.65% or 40,743.77 ha of rice fields have been identified, the remaining 6.35% consists of others, food fields, built-up areas and water bodies.